Investigating the construct measured by banked gap-fill items: Evidence from eye-tracking. (January 2018) - McCray, Gareth; Brunfaut, Tineke
This study investigates test-takers' processing while completing banked gap-fill tasks, designed to test reading proficiency, in order to test theoretically based expectations about the variation in cognitive processes of test-takers across levels of performance. Twenty-eight test-takers' eye traces on 24 banked gap-fill items (on six tasks) were analysed according to seven online eye-tracking measures representing overall, text and task processing. Variation in processing was related to test-takers' level of performance on the tasks overall. In particular, as hypothesized, lower-scoring students exerted more cognitive effort on local reading and lower-level cognitive processing in contrast to test-takers who attained higher scores. The findings of different cognitive processes associated with variation in scores illuminate the construct measured by banked gap-fill items, and therefore have implications for test design and the validity of score interpretations.